Comprehensive Midwifery Care for Mrs "M" with Anemia at the Caile Community Health Center, BuIukumba Regency: Asuhan Kebidanan Komprehensif pada Ny ‘‘M’’ dengan Anemia di Puskesmas Caile Kabupaten BuIukumba - Rosmina Anisa,; Erniawati,; Jusni,; Ariani, (Jurnal Midwifery, 2023)
Introduction Anemia or lack of iron which is needednfor thenformation of red bloodncells is one of the complicated nutritional problems faced by Indonesia today. Malnutrition in pregnant women is still a problem that must be addressed (hemoglobin). For this reason, research was carried out with the aim of this research being to carry out comprehensive midwifery care management for Mrs ''M'' with Anemia at the CaiIe Health Center, BuIukumba Regency. Method The subject used in this study was one of the third trimester pregnant women who had anemia, then comprehensive care would be carried out such as care for pregnant women, care for postpartum women, care for postpartum women, care for infants and care for family planning (KB). . This research data collection technique consists of interviews, observation, and documentation. result The results of this study are objective data from pregnant women in good overall health, calm consciousness, and HB 8 gram%. The diagnosis from the results of the data is that Ny. M experienced mild anemia during pregnancy was reached in BuIkumba in 2022. During the puerperium given to Mrs.M during the visit thenresults of thenexamination showednthat the mother's condition was normal, involution was good, there was no infection in the incision suture, TFU 2 fingers below the middle . As well as the family planning care given to Mrs. M, went smoothly. Conclusion this study is that Mrs M's healthy living standards in midwifery management can be said to have improved even though at first Mrs. M is anemic but in a light period.